2021
DOI: 10.52922/ti78320
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prolific live streaming of child sexual abuse

Abstract: Technologically enabled crime has proliferated in recent years. One such crime type is the live streaming of child sexual abuse (CSA). This study employs a machine learning approach to better understand the characteristics of Australians who engaged with known facilitators of CSA live streaming in the Philippines. This model demonstrated notable success in identifying the individuals who would engage in a high number of transactions with known facilitators. Individuals engaged in high-volume live streaming typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Characteristics. Regarding the characteristics, Cubitt et al (2021) analyzed the age of offenders of LSCSA and found that ages ranged from 20 to 76 years, and the average age of the offender was 52 years. Other studies have shown a range of between 50 and 60 years and 42 and 72 years of age (Brown et al, 2020;Napier et al, 2021a).…”
Section: Offendersmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics. Regarding the characteristics, Cubitt et al (2021) analyzed the age of offenders of LSCSA and found that ages ranged from 20 to 76 years, and the average age of the offender was 52 years. Other studies have shown a range of between 50 and 60 years and 42 and 72 years of age (Brown et al, 2020;Napier et al, 2021a).…”
Section: Offendersmentioning
confidence: 99%
“…These studies have used the same data source to some extent, and it is therefore unclear if there is any overlap in their findings. A distinction was made between low-volume and high-volume offenders (Cubitt et al, 2021). High-volume offenders were the 10% of the data sample with the highest number of transactions.…”
Section: Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several additional variables were generated for analysis. A prolific livestreaming variable was produced, as suggested by Cubitt et al (2021). It was unusual for CSA live-streaming offenders to transact more than 20 times.…”
Section: Additional Variablesmentioning
confidence: 99%
“…However, the harm to victims of technologically enabled abuse is substantial, and consistent with contact offenses (Puffer et al, 2014). Although some analytical evidence has emerged (Brown et al, 2020; Cubitt et al, 2021), the technologically and financially enabled nature of these offenses (Europol, 2019) mean data are difficult to obtain, and when available, samples are often small.…”
Section: Introductionmentioning
confidence: 99%